He Yokal Himago: A Sociological Review of Law on Nikah Siri in The Dani Muslim Community, Papua - Haryanto, Eko; Wahib, Moh; Faisal, Faisal; Islamy, Athoillah (Al-Adalah: Jurnal Hukum dan Politik Islam, 2024)
This qualitative study intends to identify and explore the trigger factors for the practice of nikah he yokal himago (nikah siri) in the dani tribal mulsim community in Jayawijaya, Papua. This qualitative study uses an empirical legal approach. The theory of effectiveness by Sarjono Soekanto became a theory of analysis. Data collection techniques use observation and interviews. Meanwhile, data analysis uses reduction, presentation, and verification. This study concludes that the factors of he yokal himago marriage vary, among others, the weak legal culture that assesses he yokal himago marriage has implications for financial attachment and social prestige for the woman. Then the low legal awareness that considers marriage as a private matter, and also yokal himago can be a solution for marriage that gets formal legal barriers. Furthermore, the role of non-legal legal structures is in the form of the role of religious figures in the implementation of he yokal himago marriage. The theoretical implications of this study show that serial marriage can be triggered by the complexity of the factors behind it, both socioeconomic, cultural, legal and religious. Â The limitations of this study have not examined the obstacles or challenges of government agencies, religious leaders and community leaders in preventing or minimizing he yokal himago marriage in the Dani tribal Muslim community in JayawijayaÂ